Pneumococcal Meningitis Vaccine Breakthroughs and Failures After Routine 7-Valent and 13-Valent Pneumococcal Conjugate Vaccination in Children in France. Issue 10 (October 2015) - Godot, Cécile; Levy, Corinne; Varon, Emmanuelle; Picard, Capucine; Madhi, Fouad; Cohen, Robert
<x xml:space="preserve">Abstract</x> We collected cases of pneumococcal meningitis vaccine breakthrough (VBT) and vaccine failure (VF) from 2003 to 2013 after the implementation of pneumococcal conjugate vaccines (PCVs) in France. VBT accounted for 3.2% of the cases (PCV7 era: 24 of 943, PCV13 era: 15 of 290) and VF 0.6% (PCV7 era: 6 of 943, PCV13 era: 2 of 290). VBT and VF are rare and occur in most cases in children younger than 2 years. The serotype 19F was the most frequent cause even after the introduction of PCV13.